2018
DOI: 10.29399/npa.22873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylphenidate on reaction time in children with Attention Deficit Hyperactivity Disorder

Abstract: Introduction: Attention-deficit/hyperactivity disorder (ADHD) is associated with a broad range of neuropsychological impairments that are attenuated with methylphenidate (MPH) treatment. The aim of this study was to determine how MPH effects attentional functioning in terms of reaction time (RT) in ADHD.Methods: Eighteen pre-medicated ADHD children (7 to 12 years old) and eighteen gender matched normal controls (7 to 12 years old) were included in the study. Participants performed an auditory attention task an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…This study was designed to investigate effectiveness of MPH medication treatment in children with ADHD by using information from changes in the concentration of oxygened haemoglobin and neuronal activity of frontal lobe during auditory oddball paradigm. We have previously shown that MPH reduced reaction times to stimuli and attenuated omission errors during the task in ADHD group [31]. The data presented here extend this finding to the prediction of robust treatment response to the MPH by multimodal EEG/ fNIRS system.…”
Section: Discussionsupporting
confidence: 80%
“…This study was designed to investigate effectiveness of MPH medication treatment in children with ADHD by using information from changes in the concentration of oxygened haemoglobin and neuronal activity of frontal lobe during auditory oddball paradigm. We have previously shown that MPH reduced reaction times to stimuli and attenuated omission errors during the task in ADHD group [31]. The data presented here extend this finding to the prediction of robust treatment response to the MPH by multimodal EEG/ fNIRS system.…”
Section: Discussionsupporting
confidence: 80%
“…Pharmacological treatment for ADHD mainly relies on psychostimulants which acts to increase synaptic levels of dopamine and noradrenaline, and have been shown to improve working memory performance as well as reduce reaction time variability [ 95 , 96 ]. ADHD has been associated with abnormal processing within attention networks and methylphenidate for example, may act to normalise this [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrates that patients with ADHD improve significantly in EF when on methylphenidate (MPH), the first-choice treatment for ADHD in the developmental age [9,10]. In particular, MPH ameliorated inhibitory control [4,[11][12][13][14], visual-spatial working memory [15], sustained and selective attention [16], and reaction times (RT) [14].…”
Section: Introductionmentioning
confidence: 99%